Histomorphometric study of testis in deltamethrin treated albino rats - Kumar, Anil (Toxicol Rep, 2014)
Deltamethrin, a type II synthetic pyrethroid, has lead to a widespread concern over the potential adverse effects on human health. Adult Wistar albino rats, weighing 150–200 g, were divided into two groups of ten animals each. The group II rats were injected with deltamethrin (1 mg/kg body weight) intraperitoneally, for five days/week for a month. The group I were controls. Animals were sacrificed within 24 h of the last injection by perfusion under anesthesia. Paraffin sections (8 μm) were cut, and stained with hematoxylin and eosin. Histomorphometry was done. There was a decrease in the body weight but increase in the weight of the testis of rat. The mean vertical, antero-posterior and transverse diameter of the testis is reduced. The basement membrane enclosing the seminiferous tubules appeared thickened at sites. The number of seminiferous tubules per unit area is statistically significantly reduced. There was a generalized significant decrease in the diameter and the epithelium thickness (height) of the seminiferous tubules, associated collapse and distortion at sites of the tubules predominantly in the central region. The data obtained in the present work suggest that gonadal (testis) changes could seriously affect the reproductive potential of the rat.